Biodiversity of Convolvulaceous species that contain ergot alkaloids, indole diterpene alkaloids, and swainsonine. (October 2019) - Cook, Daniel; Lee, Stephen T.; Panaccione, Daniel G.; Leadmon, Caroline E.; Clay, Keith; Gardner, Dale R.
Abstract: Convolvulaceous species have been reported to contain several bioactive principles thought to be toxic to livestock including the calystegines, swainsonine, ergot alkaloids, and indole diterpene alkaloids. Swainsonine, ergot alkaloids, and indole diterpene alkaloids are produced by seed transmitted fungal symbionts associated with their respective plant host, while the calystegines are produced by the plant. To date, Ipomoea asarifolia and Ipomoea muelleri represent the only Ipomoea species and members of the Convolvulaceae known to contain indole diterpene alkaloids, however several other Convolvulaceous species are reported to contain ergot alkaloids. To further explore the biodiversity of species that may contain indole diterpenes, we analyzed several Convolvulaceous species (n = 30) for indole diterpene alkaloids, representing four genera, Argyreia, Ipomoea, Stictocardia, and Turbina, that had been previously reported to contain ergot alkaloids. These species were also verified to contain ergot alkaloids and subsequently analyzed for swainsonine. Ergot alkaloids were detected in 18 species representing all four genera screened, indole diterpenes were detected in two Argyreia species and eight Ipomoea species of the 18 that contained ergot alkaloids, and swainsonine was detected in two Ipomoea species. The data suggest a strong association exists between the relationship of the Periglandula species associated with each host and the occurrence of the ergot alkaloids and/or the indole diterpenes reported here. Likewise there appears to be an association between the occurrence of the respective bioactive principle and the genetic relatedness of the respective host plant species. Highlights: Convolvulaceous species (n = 30) were screened for fungal symbiont derived compounds. Ergot alkaloids were detected in 18 species representing four genera. Indole diterpenes were detected in two Argyreia species and eight Ipomoea species. Swainsonine was detected in two Ipomoea species.